Efektivitas Fungsi Pengawasan Badan Permusyawaratan Desa Terhadap Pelaksanaan Pembangunan Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Andi M. Idris; Jamri Jamri; Ali Azhar (Journal of Innovative and Creativity (Joecy), 2026)
The principle of the rule of law under Article 1(3) of the 1945 Constitution of the Republic of Indonesia demands an effective supervisory mechanism in governance, including at the village level. The Village Consultative Body (Badan Permusyawaratan Desa/BPD) holds a strategic position as a check-and-balance institution over the village head under Article 55 of Law Number 6 of 2014 on Villages, particularly in overseeing development funded through Village Funds. This study aims to analyze the implementation of the BPD's supervisory function over village development in Pengalehan Keritang Village, Indragiri Hilir Regency, to identify the factors influencing its effectiveness, and to formulate optimization measures. The research employs a normative legal method with a library research approach, using primary, secondary, and tertiary legal materials analyzed descriptively and interpretatively. The findings reveal that although the regulatory framework governing BPD supervision is well established, its implementation in the study location remains suboptimal due to the limited capacity of BPD members, weak coordination with the village government, low community participation, and insufficient budget transparency. This gap between norms and practice undermines the accountability of village development. Optimization is recommended through capacity building for BPD members, strengthened institutional communication, digitalization of budget information, and enhanced community participation to achieve good governance at the village level.